Uptake of acid black 210 dye by organo-montmorillonite clay minerals - Volzone, Cristina (2013)
Two clays rich in montmorillonite were modified and used as adsorbents. The clay minerals were modified with hexadecylpyridinium cation (HDP+) in order to obtain organomontmorillonites,which were used for retaining acid black 210 dye from water solution. This dye is frequently used in tanning industry. The retentions of the anionic dye by organomontmorillonites were evaluated by using complete UV‐visible spectrum, analyzing the concentrations of dye solutions before (50 mg/L) and after the contact with the adsorbent. The solids were characterized by X‐ray diffraction (XRD) and infrared analyses (FT‐IR). The interlayer spacing of the montmorillonites increased, after organic cation exchange, from 13.0‐14.9 Å to 19.0‐22.0 Å and allowed the uptake of acid black 210 dye. The most disordered arrangement of HDP in montmorillonite, deduced by XRD and FT‐IR analyses, was better for higher retentions of acid black dye.